Pendidikan Karakter Berbasis Sholawat (Studi Peran ISHARI dalam Membentuk Generasi Z) - Lutfi Wahyu Hidayat; Amrini Shofiyani (Lembaga Yasin AlSys, 2026)
Although studies on character education and religious arts have received attention, discussions that specifically examine the role of Ikatan Seni Hadrah Indonesia (ISHARI) in shaping the character of Generation Z through sholawat-based activities remain limited. This study aims to analyze the role of ISHARI in shaping the character of Generation Z and to identify the challenges faced in implementing its programs. This study used a descriptive qualitative approach with a field study design. The research informants included the leaders, administrators, and members of ISHARI NU Megaluh Sub-Branch, Jombang, who were selected purposively. Data were collected through interviews, observation, and documentation, and were then analyzed using thematic analysis techniques. The results showed that ISHARI played a significant role in instilling religious values, discipline, responsibility, and noble character through regular hadrah practice, sholawat recitation, social bonding, and inter-branch joint activities. The main challenges in program implementation included limited practice time, lack of discipline among young members, trainer delays, competition with other organizations such as pencak silat, and limited funding. These findings strengthen the understanding of Islamic art as a medium for moral development and contribute to the development of studies on sholawat-based character education. The conclusion of this study emphasizes that ISHARI sholawat activities play an important role in fostering the spiritual and moral values of Generation Z. The implications of this study include theoretical contributions to the literature on Islamic education and practical recommendations for ISHARI administrators to develop more innovative mentoring methods and strengthen program sustainability both institutionally and economically.